A Survey Among Audiences of Subtitled Films in Viennese Cinemas - Widler, Brigitte (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractA survey was conducted in Vienna in 2002 to get answers to questions concerning the target audience for subtitled films.